Pathomechanics, Diagnosis and Treatment of Traumatic Injuries to the Ankle and Subtalar Joints in the Scientific Achievements of the Department of Trauma Surgery and Orthopaedics at the 5th Military Clinical Hospital with Polyclinic, Independent Public Healthcare Centre in Krakw - Piotr Golec; Katarzyna Haładus; Edward Golec (Rehabilitacja Medyczna, 2022)
Introduction: Traumatic injuries to the ankle and subtalar joints constitute severe damage to the locomotor system, both structural and functional. They most often occur in the form of ankle fractures and sprains of the ankle joint, and the least common are peritalar dislocations.Study aim: The aim of the study was to answer the following research questions: 1. What are the most common causes of traumatic injuries to the ankle and subtalar joints, and what are the most common causes of these injures?; 2. What diagnostic methods of traumatic injuries to the ankle and subtalar joints in the analysed period of clinical observation dominated in their imaging?; 3. What are the recommended treatments for traumatic injures of the ankle and subtalar joints?Materials and methods: The aim of the study was carried out on the basis of analysing publications and conference presentations regarding traumatic injuries by employees of the Department of Trauma Surgery and Orthopaedics, the 5th Military Clinic Hospital with Polyclinic, Independent Public Healthcare Centre in Krakw, covering the years from 1992 to 2017. The research methodology, on the other hand, was based on analysis of the content concerning thematically compatible publications and scientific studies with the adopted objectives of the work and established research questions. In the study, 2 thematic monographs (books) were also included, which were published by Pastwowy Zakad Wydawnictw Lekarskich (PZWL) [Eng. National Institute of Medical Publishing] in 2020 and 2021 by a retired clinic employee. They are partly based on its clinical material from 1992 to 2017.Results: In the analysed period, 58 of the identified scientific studies were thematically consistent with the adopted research objectives and established research questions. Those were 20 original creative papers (34.5%), 3 review papers (5.2%), 4 case studies (6.9%), 1 postdoctoral dissertation (1.7%), 4 doctoral dissertations (6.9%) and 1 (1.7%) thematic monograph (book), 11 (18.9%) chapters in thematic monographs (book) and 14 (24.2%) conference and convention presentations.Conclusions: 1. The most common causes of traumatic injuries to the ankle and subtalar joints are so-called sports-related injuries or those caused by traffic accidents as well as falls on a hard surface at the same level, especially in people with bone tissue demineralisation disorders. Most often, they are in the form of ankle fractures, and the least common are peritalar dislocations. 2. Clinical diagnosis of traumatic injuries to the ankle and subtalar joints requires manual tests regarding their stability, and imaging examinations are based primarily on ultrasound, MRA and MRI. With regard to post-traumatic instability of the ankle joint, these diagnostics require radiological examination in forced positions. 3. Fractures of the ankle-shin joint require surgical treatment based on the open reposition of bone fragments and their effective stabilisation, as well as on the fixation of tibiofibular syndesmosis. On the other hand, peritalar dislocations can be treated non-operatively, while selected types of damage can be treated surgically. A necessary supplement to the treatment of the traumatic injuries in question is a consistently implemented and individualised programme of physiotherapy.